2000
DOI: 10.1108/09513540010344731
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors in online education

Abstract: The Internet is a major technological advancement reshaping not only our society but also that of universities worldwide. In light of this, universities have to capitalise on the Internet for teaching, and one progressive development of this is the use of online delivery methods. This paper draws upon the results of a survey conducted amongst students enrolled in one online management course at an Australian university. Three critical success factors in online delivery are identified: technology, the instructo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
379
1
37

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 622 publications
(476 citation statements)
references
References 14 publications
12
379
1
37
Order By: Relevance
“…This study was looking at two factors of social integration in Tinto's SIM and has introduced the Student Online Learning Readiness (SOLR) conceptual model with the purpose of extending Tinto's social integration to an online learning environment. The significant influences of social competencies (Chen et al, 2010;Parker et al, 2006;Williams, 2003), communication competencies (Betermieux & Heuel, 2009;Dabbagh, 2007;Dabbagh & Bannan-Ritland, 2005;Volery & Lord, 2000;Williams, 2003), and technical competencies (Osika & Sharp, 2002;Selim, 2007;Watulak, 2012;Whale, 2006) have been verified by previous research. Therefore, it is now found to be possible to measure the levels of learners' social, communication, and technical competencies through use of the Student Online Learning Readiness (SOLR) instrument before the learners take an online course.…”
Section: Final Four-factor Structurementioning
confidence: 58%
See 1 more Smart Citation
“…This study was looking at two factors of social integration in Tinto's SIM and has introduced the Student Online Learning Readiness (SOLR) conceptual model with the purpose of extending Tinto's social integration to an online learning environment. The significant influences of social competencies (Chen et al, 2010;Parker et al, 2006;Williams, 2003), communication competencies (Betermieux & Heuel, 2009;Dabbagh, 2007;Dabbagh & Bannan-Ritland, 2005;Volery & Lord, 2000;Williams, 2003), and technical competencies (Osika & Sharp, 2002;Selim, 2007;Watulak, 2012;Whale, 2006) have been verified by previous research. Therefore, it is now found to be possible to measure the levels of learners' social, communication, and technical competencies through use of the Student Online Learning Readiness (SOLR) instrument before the learners take an online course.…”
Section: Final Four-factor Structurementioning
confidence: 58%
“…Cho and Jonassen (2009) found that there is a significant correlation between success in online learning environments and the student's social competencies in interacting with his or her instructor and peers in online courses. Second, a sizeable number of studies have proposed that interpersonal and communication competencies are the most influential predictors of academic achievement (Betermieux & Heuel, 2009;Dabbagh, 2007;Dabbagh & Bannan-Ritland, 2005;Volery & Lord, 2000;Williams, 2003). Third, technical competencies are considered to be a necessary component for successful learning experiences in online education (Osika & Sharp, 2002;Selim, 2007;Watulak, 2012;Whale, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Σέινο, επηηξέπεη ηελ θαηεγνξηνπνίεζε θαη ηελ αλαδήηεζε ησλ καζεκάησλ. Σα πεξηζζφηεξα εθπαηδεπηηθά ηδξχκαηα πνπ επηιέγνπλ ην Moodle σο κέζν γηα ηελ εμ απνζηάζεσο δηαδηθηπαθή εθπαίδεπζε, επηθεληξψλνπλ ηα νθέιε ζε ηέζζεξα πεδία (Volery, 2004): α) επέθηαζε ηεο πξνζβαζηκφηεηαο (expanding access), β) άξζε ησλ πεξηνξηζκψλ ρσξεηηθφηεηαο (alleviating capacity constraints), γ) εθκεηάιιεπζε ησλ αλαδπνκέλσλ επθαηξηψλ ζηελ αγνξά, θαη δ) θαηαιπηηθή ιεηηνπξγία γηα ηελ αλακφξθσζε ησλ αθαδεκατθψλ ζεζκψλ. Πξνζθέξνληαο εμ απνζηάζεσο εθπαίδεπζε κε απηφλ ηνλ ηξφπν, επηηπγράλεηαη ε ζπκκεηνρή ζπνπδαζηψλ απφ απνκαθξπζκέλεο πεξηνρέο, ζε δηάθνξα επηζηεκνληθά επηζηεηά.…”
Section: ζ γηαγηκστακζ δφαρμογζ Moodle καη ζ αξηοποηζ ζ σζunclassified
“…These alternatives, called online learning education, became available with the development of a reliable mail delivery system during the late nineteenth century (Ascough, 2002;Rumble, 2001). Distance learning has been defined as any approach to education delivery that replaces the same time, same place, face to face environment of a traditional classroom (Volery & Lord, 2000). According to this definition, distance education can take many forms such as mail correspondence, open and closed circuit audio and video presentations, telephone communications, and the increasingly popular Internet.…”
Section: Literature Reviewmentioning
confidence: 99%